Different Roles of Resident and Non-resident Macrophages in Cardiac Fibrosis - Hu, Siyuan; Yang, Meng; Huang, Shumin; Zhong, Senjie; Zhang, Qian; Ding, Haichao; Xiong, Xiajun; Hu, Zhixi; Yang, Yi (Frontiers in Cardiovascular Medicine, 2022)
Cardiac fibrosis is a key pathological link of various cardiovascular diseases to heart failure. It is of great significance to deeply understand the development process of cardiac fibrosis and the cellular and molecular mechanisms involved. Macrophages play a special role in promoting heart development, maintaining myocardial cell homeostasis and heart function. They are involved in the whole process from inflammatory to cardiac fibrosis. This article summarizes the relationship between inflammation and fibrosis, discusses the bidirectional regulation of cardiac fibrosis by macrophages and analyzes the functional heterogeneity of macrophages from different sources. It is believed that CCR2- cardiac resident macrophages can promote cardiac function, but the recruitment and infiltration of CCR2+ cardiac non-resident macrophages aggravate cardiac dysfunction and heart remodeling. After heart injury, DAMPs (damage associated molecular patterns) are released in large quantities, and the inflammatory signal mediated by MCP-1 (macrophage chemoattractant protein-1) promotes the infiltration of CCR2+ monocytes and transforms into macrophages in the heart. These CCR2+ non-resident macrophages not only replace part of the CCR2- resident macrophage subpopulation in the heart, but also cause cardiac homeostasis and hypofunction, and release a large number of mediators that promote fibroblast activation to cause cardiac fibrosis. This article reveals the cell biology mechanism of resident and non-resident macrophages in regulating cardiac fibrosis. It is believed that inhibiting the infiltration of cardiac non-resident macrophages and promoting the proliferation and activation of cardiac resident macrophages are the key to improving cardiac fibrosis and improving cardiac function.